APPLICATION OF THE CUSTOMER SATISFACTION INDEX (CSI) TO TRANSPORT SERVICES (Perner's Contacts, 2010)
This submission deals with a possibility of transport service evaluation using the customer satisfaction index (CSI), because this index is abroad often used just for the quality of service evaluation, what is for this product difficult problem.
Keywords: Customer satisfaction; customer satisfaction index; quality criteria; satisfaction; dissatisfaction